IR-Photometry Method for Measuring Glucose Concentration in Peritoneal Dialysis Fluid - N. M. Zhilo; M. O. Mikhailov; E. L. Litinskaia; K. V. Pozhar (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The transition of glucose into the blood during automated peritoneal dialysis with regeneration of the dialysis fluid leads to a decreased removal of excess fluid from the body and corresponding violations of the water-salt balance.Aim. To consider a system for automatically maintaining the concentration of glucose in the dialysate solution, which provides effective ultrafiltration, as well as to propose a non-contact photometric feedback sensor.Materials and methods. The sensor is an optical system of an IR laser diode with a power of 30 mW and a wavelength of 1600 nm, a photodiode and a quartz tube, through which the test solution circulates. The sensor measures the attenuation of the radiation passing through the solution in a pulsed mode and calculates the glucose concentration. The selected combination of digital filters provides compensation for the noise of the optical system. Experimental studies of the efficiency of the sensor were carried out on peritoneal dialysis solutions with various concentrations of urea, creatinine, uric acid and glucose. At the beginning of the experiments, the sensor was calibrated in a pure solution.Results. It was shown that the developed sensor makes it possible to measure the concentration of glucose in a solution for peritoneal dialysis in the range of 42…220 mmol / l with a relative error of about 15%. The time of one measurement is about 1 minute, which makes it possible to obtain up-to-date information on the current concentration of the solution.Conclusion. This combination of characteristics will allow the sensor to be used in artificial kidney wearable devices for assessing the glucose content in the solution, calculating the time to change the solution and as a feedback sensor in a system for maintaining the concentration of the osmotic agent.